Narrating the 2015 Nepal Earthquake: Experiences, Disaster Subjectivities, and Resistant Agency - Rai, Bhim Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This paper examines the detailed narratives and experiences of survivors of the 2015 Nepal earthquake, capturing their vivid accounts of where they were, what they felt, and how they reacted in the immediate aftermath. Drawing on local people’s embodied narratives as a crucial site of disaster memory, it illustrates how storytelling becomes a means through which they make and remake their post-disaster world inhabitable and comfortable again. These narratives offer insights into how solidarity and unity initially shaped survival efforts and reveal how, as large-scale aid began to arrive, perceptions of unfairness, injustice, and fraud in its distribution led to growing dissatisfaction among villagers. In doing so, the paper further shows how relief distribution deepened social divisions, reinforcing Tol (area) membership as a criterion for receiving aid and fragmenting the community into lower and upper Tol. Based on ten months of ethnographic research—including semi-structured interviews and key informant interviews—conducted for my PhD dissertation between 2019 and 2024 in the villages of Kot, Gunsa, and Dhap (Panchpokhari Thangpal Rural Municipality, Sindhupalchok), this ethnography contributes to disaster anthropology in Nepal. It examines how locals collectively experienced suffering (pain as subjectivity) and, crucially, how they transformed this suffering into an agentive force. Rather than remaining passive aid recipients, they deployed their extended kinship networks to counteract social divisions and mitigate suffering during the aid distribution process. .